A study of returned medication; comparison between Unit-of-Dose (UoD) system and Unit-of-Use (UoU) system in medical wards, Hospital Putrajaya - Mohamed, Nur Liyana; Shabudin, Nur Zuriana; Hamrah, Siti Hajar Aisyah (2011)
Introduction; Unit-of-Dose (UoD) system has begun its implementation in Hospital Putrajaya since June 2010 which started with the Surgical Wards (3A and 3B) and later expanded to the Medical Wards (4A and 4B). This new system is the preferable system in many hospitals due to its many advantages. There are numerous studies highlighted the effectiveness of Unit-of-Dose in reducing medication return, total drug/cost lost and medication error. This study was conducted to compare between Unit of Dose and Unit of Use in relation to return medication. Methodology: A prospective study was carried out in Medical Wards (4A and 4B) by reviewing the number of items returned to the pharmacy pre- and post-UoD's, from October to December 2010. The data was collected from the medical wards (4A and 4B) since this wards are in the process of transformation from Unit of Use system to Unit of Dose system according to the standard procedures applied in Hospital Putrajaya. Data were recorded in the data collection form and analyzed using Microsoft Excel. Result:From this study, the total percentage of reduction of cost loss in 4A ward is 68.67% while the total percentage of reduction of cost loss for 4B ward is 95.07%. In this study, the total cost loss and cost save between the UoU and UoD system are about the same for both wards 4A and 4B. The cost loss is lower in UoD system compared to UoU system as most of the medication from UoD system can be reused as they are packed individually. Meanwhile for the cost save, the reading is higher in UoU system. This is due to the large quantity of the returned medication as the medication was supplied for a day's supply or for a complete course. Plus, it is lower in UoD system as the rate of patients' compliance is higher in UoD system as most of the medication is in ready-toadministered form. It is easier for the pharmacist and staff nurse involve. In conclusion, it has been show11 that UoD did incurred a significant reduction in medication return which can be deduced to the reduction of cost borne by the hospital in purchasing medications.